Fósforo em latossolo do estado de Minas Gerais: II - Quantidade de fósforo e fósforo "disponível" - F C Bahia Filho, Antônio; Braga, José Mário (Revista Ceres, 2025)
Samples of surface horizions of twenty latosols in the State of Minas Gerais were analyzed for inorganic phosphate content and available phosphorus by using the following extractors: Bray 1, IAC, Mehlich, and Olsen.